1996
DOI: 10.1159/000154368
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Genetics of Dehydroepiandrosterone Sulfate and Its Relation to Possible Cardiovascular Disease Risk Factors in Mexican Americans

Abstract: Dehydroepiandrosterone sulfate (DHEAS) is an adrenal steroid which has been inversely associated with development of atherosclerosis. We estimated heritability of serum DHEAS levels in 564 related Mexican Americans. We found a significant heritability for DHEAS (h2 = 0.39, p < 0.001). Measures of alcohol consumption, reproductive status, body composition, and HDL3 levels showed significant relationships with serum DHEAS levels. Sex and age were significantly associated with the mean, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In the Honolulu Heart Program, among Japanese-American men, hypertension continued to be significantly associated with an increased risk of hemorrhagic and thromboembolic stroke for all age groups up to 65–74 years, whereas a significant positive association was not found in the group from 75–93 years of age [14]. A prospective cohort study in the USA found that the relative risk of stroke in relation to hypertension decreased from 4.0 at the age of 50 years to unity at the age of 90 years [12]. On the other hand, another cohort study in Sweden showed that systolic but not diastolic blood pressure was significantly related to an increased risk of stroke in subjects aged 85–88 years [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Honolulu Heart Program, among Japanese-American men, hypertension continued to be significantly associated with an increased risk of hemorrhagic and thromboembolic stroke for all age groups up to 65–74 years, whereas a significant positive association was not found in the group from 75–93 years of age [14]. A prospective cohort study in the USA found that the relative risk of stroke in relation to hypertension decreased from 4.0 at the age of 50 years to unity at the age of 90 years [12]. On the other hand, another cohort study in Sweden showed that systolic but not diastolic blood pressure was significantly related to an increased risk of stroke in subjects aged 85–88 years [15].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is a well-established risk factor for stroke in the middle-aged in both western and Asian countries [7,8,9,10,11]. Several studies in western countries indicated that the increased risk of stroke associated with hypertension weakened with advancing age [12,13,14,15]. The Framingham study demonstrated that systolic blood pressure was positively associated with the risk of stroke in a population ranging in age from 55 to 84 years at baseline [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic and environmental correlations between the age-and sex-adjusted measures of brain anatomy and BPs were estimated by variance decomposition using maximum likelihood methods, 12 and phenotypic correlations between traits were calculated based on the genetic and environmental correlations. 13 Univariate and bivariate quantitative linkage analyses were performed using the Expectation Maximization Variance Components software program, 14 which uses a multivariate variance components approach that is an extension of the univariate approach described by Amos 15 and de Andrade et al 16 The multipoint identity-by-descent sharing among pairs of relatives were calculated using the SIM-WALK2 software program, which estimates multipoint identity-bydescent probabilities using an alternate Markov chain Monte Carlo algorithm that accommodates large sibships and provides estimates in agreement with deterministic methods. 17 Calculations were based on the pedigree relationships for 1413 of the original GENOARochester participants in whom measurements of genome-wide markers were available.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Adjustments for sex, age, and total intracranial volume (for brain atrophy and ventricular volume) or brain volume (for leukoaraiosis) were incorporated as co-variates in the genetic models. Genetic and environmental correlations between the adjusted (transformed) trait values were estimated by means of variance decomposition using maximum likelihood methods,13 and phenotypic correlations between traits were calculated on the basis of genetic and environmental correlations 14. Sibship structure was verified using the MERLIN software program 15.…”
Section: Methodsmentioning
confidence: 99%